Masculinized female yellow-bellied marmots initiate more social interactions - Monclús, Raquel (The Royal Society, 2012)
The presence of male siblings in utero influences female morphology and life-history traits because testosterone transferred among foetuses may masculinize females. Similarly, litter sex composition might alter the display of sexually dimorphic behaviour, such as play and allogrooming, since they are modulated by androgens. We explored whether masculinization alters the frequency of play and sociopositive behaviour in female yellow-bellied marmots (Marmota flaviventris). We found that masculinized juvenile females were more likely to initiate play and allogrooming, but yearling females exhibited higher levels of oestrogen-modulated sociopositive behaviours. Additionally, the more they interacted, the greater number of different partners they interacted with. Our results suggest that masculinization increases the rate of age-dependent social behaviour. This probably works by increasing exploration that predisposes individuals to higher encounter rates. Further support comes from previous findings showing that masculinized females were more likely to disperse. Our study stresses the importance of considering litter sex composition as a fitness modulator.